The scientific map of medicine in Iran: Category co-citation analysis - Hariri, Nadjla; Maryam, Shekofteh (Malaysian Journal of Library and Information Science, 2017)
Hariri, N., & Shekofteh, M. (2013). The scientific map of medicine in Iran: Category co-citation analysis.Â Malaysian Journal of Library & Information Science,Â Vol.18, no. 2:Â 79-94. Recognition and having a general outlook of the researches performed, as well as the links amongÂ various fields, and also having awareness of the developments and progression of such fields in timeÂ are among the objectives of scientific maps. The goal of the present study is to discover and drawÂ the scientific map of medical domains in Iran during 2003-2007. For such purposes, we sought toÂ utilize the subject category co-citation analysis. In line with this, the most productive, effective andÂ the most cited medical subject categories in the period under investigation were determined. TheÂ study population included all scientific papers published by Iranians in medical subject categories, as well as their references, which have been indexed in Science Citations Index Expanded (SCIE). DataÂ analyses and mapping were performed using Network Workbench (NWB) tool. The findings showÂ that Iranian medical scholarly publications have been increasing compared with its total scientificÂ products. The mappings reveal more density in the maps of each successive year under study. It canÂ be said that subject categories such as Medicine, General & internal, Pharmacology & pharmacy,Â and Biochemistry & molecular biology are among the most productive categories as they have moreÂ relations with other categories. There is a significant difference between the quantity of scientific products and the amount of citations garnered by effective categories and other medical categories.Â However, no significant difference is found between the mean received citations per article inÂ effective medical categories and other categories. The authors recommend more attention be paidÂ to the scientific mappings using various techniques applied in different years in Islamic countries.